Pragmatic Particles in The Javanese Language in The Banyumasan Comedy “Peang Penjol” - Nur Halimah; Novika Stri Wrihatni (Edunity Kajian Ilmu Sosial dan Pendidikan, 2026)
Particle is a form of words that have limited freedom but have the status of common words. Particle in Javanese is not just a suffix, but a tool to convey expressions, emphasis, and hidden intentions from the speaker. In this study, it was found that there is a difference in the use of mbok particles in the Javanese language of the Banyumas dialect which serves as a confirmation of a speaker's suspicion about a fact. With this, this research focuses on the study of pragmatic particles. The purpose of this study is to show the distribution and use of pragmatic particles in the Javanese dialect of Banyumasan. The source of data for this study is an oral data corpus in the form of Dagelan Banyumasan Peang Penjol. The method used in this study was the distribution method using techniques for direct elements and reverse techniques. The results of the study showed that the use of pragmatic particles in the Javanese language of the Banyumasan dialect functions as a marker of emphasis, astonishment, confirmation of suspicion, and affirmation of commands. In conclusion, the distribution of pragmatic particles is highly flexible, influenced by syntax and intonation, and their meaning depends on context and position. This research also reveals that the mbok particle functions not only as an expression of hope but also as a confirmation of the speaker's suspicion. Thus, pragmatic particles are essential linguistic tools for conveying attitudes, emotions, and communicative intentions.